Isolation of potent alpha-glucosidase inhibitor from a novel marine bacterium Arthrobacter enclensis - Mawlankar, Rahul B.; Dharne, Mahesh S.; Dastager, Syed G. (SN Applied Sciences, 2020)
Alpha-glucosidases are involved in the hydrolyzation of glycosidic bond of di- or oligo-saccharides into mono-saccharides, thus help in the breakdown and absorption of sugars. Inhibition of alpha-glucosidases by inhibitors tend to slow break down and release of sugars into the bloodstream and can be used as therapeutic agents in the treatment of diabetes and obesity. In particular, some of the inhibitors are used in the treatment mainly acarbose, voglibose, and miglitol. In this study, we have reported the alpha-glucosidase inhibitory compound from a newly described marine bacterium Arthrobacter enclensis. The purified compound from A. enclensis was identified by HPLC, and further FTIR and tandem mass spectrometry (MS/MS) methods. The purified compound was annotated and identified by a Web tool CFM-ID (Competitive Fragmentation Modeling for Metabolite Identification). From analysis it was found that the compound showed high similarity with acarbose which is a C7N aminocyclitol compound. Further, we analyze the draft genome of A. enclensis using anti-SMASH. We observed that it matches the homology with biosynthetic gene cluster of acarviostatin and acarbose with 11% and 7% respectively. We demonstrated that, the purified compound from A. enclensis shows the inhibitory activity against alpha-glucosidase with an IC50 value of 500 ± 0.142 μg/ml as compared to standard acarbose, which showed an IC50 value of 200 ± 0.012 μg/ml. This result suggests that A. enclensis has a tendency to produce a C7N aminocyclitol like molecule which matched to acarbose and it uses different biosynthetic gene cluster for the synthesis of C7N aminocyclitol like molecule, which can be further used for the production and treatment purpose.

Insights on biorational potential of Ocimum gratissimum essential oil and its binary combination with monoterpene phenol for control of rice weevil (Sitophilus oryzae) and aflatoxigenic fungi. - Remesh, V. Archana; Raveendran, Ashika; Bincy, K.; Wagh, Vasudev S.; Dastager, Syed G.; Babu, C. S. Vivek (Food Bioscience, 2022)
Food grain storage is a difficult task due to insect infestation and subsequent mycotoxin contaminations which adversely affects the nutritional quality of grains and leading to economic loss. Current research focuses on contact and fumigant toxicity effects of essential oils (EO) and aroma compounds against Sitophilus oryzae and growth inhibition of aflatoxigenic fungi. The EO of Ocimum gratissimum comprised of thymol (46.8%), gamma-terpi-nene (14.04%) along with o-cymene (11.76%). Also, Cymbopogon flexuosus rich in citral (76.3%) and geraniol (84.6%) and Cymbopogon nardus having geraniol (49.24%) and geranyl acetate (20.9%) were all evaluated using a dose of 25 mu L (Conc-833.3 mu L/L air) against S. oryzae. All the compounds showed significant mortality (>95%) at 24 h of exposure. The insecticidal property of O. gratissimum oil chemotype showed a strong contact and fumigant toxicity against S. oryzae at a highest dose of 25 mu L (Conc-833.3 mu L/L air) within 24 h. It has been further evaluated on three aflatoxigenic fungal strains which showed reduction in growth and aflatoxin content (Aflatoxin B and G), which was markedly reduced upon the treatment. The binary mixture interaction of O. gratissimum oil with monoterpene phenol (carvacrol) was assessed and the specific binary mixture of 80:20 ratio (having additive property) acts as a contact insecticide with 100% mortality. Hence, essential oil of less explored Ocimum species (O. gratissimum) and its binary mixture could be deployed as potential biorational for control of rice weevil (Sitophilus oryzae) and aflatoxigenic Aspergillus spp.
Keywords: Aflatoxigenic fungi; Binary combination; Essential oil; Ocimum gratissimum; Sitophilus oryzae

Isolation and structural characterization of exopolysaccharide from marine Bacillus sp. and its optimization by Microbioreactor - Wagh, Vasudev S.; Said, Madhukar S.; Bennale, Jagadish S.; Dastager, Syed G. (Carbohydrate Polymers, 2022)
In the present study, a cost-effective, robust Microbioreactor based production optimization of levan like exopolysaccharide from marine Bacillus sp. SGD-03 was analysed. FE-SEM analysis has showed the significant fibrillar structure of EPS. Size exclusion chromatography and other analytical data revealed that, produced EPS has a molecular weight of 1.0 x 10(4) Da and is composed of fructose monosaccharide with hydroxyl, carbonyl, and ether groups. The backbone structure of EPS has a branching pattern of beta-(2,6) linkages which confirms the similarity with available levan like polymers. The cost-effective media composition for levan production was demonstrated. The maximum yield of crude levan obtained was 123.9 g/L by response surface methodology using robust BioLector Pro Microbioreactor, and same has been validated with shake flask, 1 L and 10 L pilot-scale fermentation.
Keywords: EPS; marine; Microbioreactor; Optimization; structure

In vitro anticancer evaluation of enceleamycin A and its underlying - Khan, Abujunaid; Pradeep, S.; Dastager, Syed G. (RSC Advances, 2023)
It has become more crucial than ever to find novel anticancer compounds due to the rise in cancer mortality and resistance to the present chemotherapeutic drugs. Naphthoquinones are regarded as privileged structures for their ability to inhibit various cancers. The current study examined three novel furo-naphthoquinones (Enceleamycins A-C) previously isolated from Amycolatopsis sp. MCC 0218 for their anticancer potential. Enceleamycin A demonstrated considerable cytotoxicity for triple-negative breast cancer (TNBC) MDA-MB-231 cells with an IC50 value of 1.25 mu g mL(-1) (3.78 mu M). It also showed the ability to inhibit MDA-MB-231 cell migration. Enceleamycin A raises intracellular ROS levels in TNBC cells, ultimately leading to apoptotic cell death, as demonstrated by Annexin V/PI staining. The molecular docking and simulation investigation revealed better binding affinity of Enceleamycin A with AKT2, which plays a vital role in breast cancer's invasiveness and chemo-resistance. Enceleamycin A inhibits the AKT2 enzyme in vitro with an IC50 value of 0.736 mu g mL(-1) (2.22 mu M), further validating the docking study. The in silico physicochemical and pharmacokinetics characteristics of Enceleamycin A demonstrated its drug-likeness. Intriguingly, Enceleamycin A is non-hemolytic in nature. Taken together, Enceleamycin A could be a candidate molecule for treating TNBC cells by targeting the AKT2 signaling pathway.
Keywords: Assay; cancer; Derivatives; Naphthoquinones; Plays